Effectiveness of Prednisolone Acetate Eye Drops 1% in Improving the Final Vision of Anterior Uveitis Patients - Anugrahsari, Santi; Celine, Callysta; Saragih, Putri Arsya; Arsana, Gabriel Ferdinan (Universitas Kristen Krida Wacana, 2024)
Anterior uveitis is the most common classification of uveitis and can result in decreased vision, even blindness in sufferers. Therefore, this literature review was carried out to determine the effectiveness of topical steroids, namely prednisolone acetate 1%, in improving final vision in anterior uveitis patients. In this literature review, 6 articles were found from electronic databases in PubMed and Google Scholar, which were selected based on the specified inclusion and exclusion criteria. The study's results stated that prednisolone acetate 1% eye drops effectively improved final vision in anterior uveitis patients. Further research regarding the effectiveness of prednisolone acetate 1% needs to be carried out in a broader scope, with various patient characteristics, to make the research results more accurate.